Modified integrated Islamic CSRD index and financial performance of Malaysian Islamic banks: stakeholders’ perception - Mohd Sofian, Fatimah Noor Rashidah; Muhamad, Rusnah (Emerald Insight, 2020)
Purpose –The purpose of this paper is to examine the relationship between the modified integrated Islamic CSRD index (MIICSRDi) and financial performance of Malaysian Islamic banks as perceived by the stakeholders.